2022
DOI: 10.3389/fpsyg.2022.815341
|View full text |Cite
|
Sign up to set email alerts
|

Board Network and CSR Decoupling: Evidence From China

Abstract: This paper investigates the influence of board network centrality on corporate social responsibility (CSR) decoupling. CSR decoupling refers to the gap between corporate internal and external actions in CSR practices. Specifically, we measure CSR decoupling as the difference between corporate social disclosure (CSD) and corporate social performance (CSP). This paper uses a sample of Chinese A-share listed firms during 2009–2018, takes the technical dimension score (T-score) and content dimension score (C-score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 87 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…According to Al‐Shammari et al (2019), CEO narcissism increases externally oriented CSR practices, whereas there is no significant impact on internally oriented CSR actions. Zhao et al (2022) found a positive relationship between board network centrality and greenwashing in the pre‐adoption period of new environmental regulations. Liu et al (2023) documented that mutual fund investors' distraction increases CSR decoupling, more pronounced by negative shocks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Al‐Shammari et al (2019), CEO narcissism increases externally oriented CSR practices, whereas there is no significant impact on internally oriented CSR actions. Zhao et al (2022) found a positive relationship between board network centrality and greenwashing in the pre‐adoption period of new environmental regulations. Liu et al (2023) documented that mutual fund investors' distraction increases CSR decoupling, more pronounced by negative shocks.…”
Section: Resultsmentioning
confidence: 99%
“…In more detail, corporate governance can be separated into board composition, ownership, and other stakeholder pressure. Regarding board composition , managerial entrenchment (Garcia‐Sanchez et al, 2020), sustainability board committees (Gull, Hussain, Khan, Khan, & Saeed, 2022), board gender diversity (Eliwa et al, 2023; Gull, Hussain, Khan, Nadeem, & Zalata, 2022), board independence and size (Yu et al, 2020), board network centrality (Zhao et al, 2022), CEO with positions as government officials (Marquis & Qian, 2014), CEO power (Gull et al, 2023; Shahab et al, 2022), CEO overconfidence (Sauerwald & Su, 2019), and CEO narcissism (Al‐Shammari et al, 2019) were included. Ownership structure was recognized as institutional ownership, (Yu et al, 2020), family ownership (Parra‐Dominguez et al, 2021), mutual fund investors' distraction (Liu et al, 2023) and institutional shareholder linkage to the central government and chair/CEO served as delegate to the two most important national political councils (Luo et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although Hexun provides ratings of overall CSR performance from 2010, the environmental dimensions of CSR performance for all listed firms have been zero since 2018 (Zhao et al, 2022; Zhong et al, 2019). Therefore, we do not use the CER ratings provided by Hexun.…”
Section: Methodsmentioning
confidence: 99%
“…CSMAR is an economic and financial database developed in conjunction with China’s current conditions. It is mainly based on the needs of academic research, drawing on the professional standards of the internationally renowned databases such as CRSP, Compustat, I/B/E/S, Thomson, etc., which are widely used in China’s relevant economic research [ 40 , 41 ]. For example, referring to the existing literature, the data of the dependent variable corporate environmental protection investment in the model come from the corporate financial statement note data in CSMAR.…”
Section: Methodsmentioning
confidence: 99%